Buckling analysis of thin-walled cold-formed steel structural members using complex finite strip method. (May 2015) - Naderian, H.R.; Ronagh, H.R.
Abstract: In this paper, a generalised complex finite strip method is proposed for buckling analysis of thin-walled cold-formed steel structures. The main advantage of this method over the ordinary finite strip method is that it can handle the shear effects due to the use of complex functions. In addition, distortional buckling as well as all other buckling modes of cold-formed steel sections like local and global modes can be investigated by the suggested complex finite strip method. A combination of general loading including bending, compression, shear and transverse compression forces is considered in the analytical model. For validation purposes, the results are compared with those obtained by the Generalized Beam Theory analysis. In order to illustrate the capabilities of complex finite strip method in modelling the buckling behavior of cold-formed steel structures, a number of case studies with different applications are presented. The studies are on both stiffened and unstiffened cold-formed steel members. Highlights: Complex FSM is proposed for buckling analysis of cold-formed steel members. Distortional buckling and other buckling modes can be evaluated by this method. The method can also handle shear forces owing to the use of complex functions. A general loading conditions can be considered in the analytical model. Capability of the complex treatment is verified by comparing with GBT method.